Peranan Profesi Penilai Publik Terhadap Penyelenggaraan Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum Dalam Proyek Strategis Nasional (PSN) Sesuai Dengan Perpres No.3 Tahun 2016 - Aprilianti, Dahlia; Wibawa, Kadek Cahya Susila (Hukum dan Masyarakat Madani, 2023)
Indonesia continues to increase economic growth by conducting the acceleration of the development of national strategic projects. The role of the appraisal profession in the National Strategic Project is needed in the denying the value of changes in loss. This study aims to analyze and provide the understanding of the role of the appraisal profession in the acceleration of national strategic projects. This research uses normative gurrent methods. The results of the study show that the role of the appraisal profession is needed in the planning stage to the stage of implementation of land procurement. The implications of the Nasoral Strategic Project should be realized that requires the readiness of the appraisal profession so that the procurement of land is increasingly reduced. The MAPPI Association can play a role in providing legal protection for each of its members in the form of cooperation of Memorandum of Understanding with the law enforcement official so that the appraiser may increase its participation in order to support national strategic projects. MAPPI can also initiate the formation of regulations related to the operation of the operations (KSO) between KJPP to improve the role of the appraisal in minimizing the ground procurement of the land as well as equity to the assessment of the assessment to all its members in Indonesia.